Critical Literacy Model On Students In Preparing Final Assignments To Avoid Plagiarism - Hayati, Kinanti Resmi; Zawawi, Zawawi; Sholihatin, Endang (Universitas Malikussaleh, 2020)
The aim of this study is to develop a Critical Literacy model for Management Economics departments Students of economics and business faculty of UPN